El Discurso de Niños y Niñas - Magana-Frade, I; Villalta-Paucar, M (Universidad Nacional Autonoma de Mexico, 2021)
This article analyzes the classroom participation experience from the perspective of both boys and girls from urban and rural sociocultural contexts in Chile. Methodologically, it is a qualitative study performed by analyzing the content of the discursive and pictorial productions of 74 first grade infants from 14 schools with high educational vulnerability, 6 of them located in the urban sector and 8 in the rural sector. We conducted 16 interviews to inquire about the student’s participation experience and we asked each of them, individually, to draw a picture of the learning activities usually carried out in the classroom. We also applied Raven s colored progressive matrix scale (MPC). The results reveal that there is a direct relation between the scored obtained in the MPC test and the classroom participation perception expressed in the drawings. We also found differences between the experiences and discourses of students from urban and rural schools. © 2021. All Rights Reserved